Meningkatkan Kinerja Guru Melalui Servant Leadership, Disiplin Kerja, Dan Budaya Organisasi - Wikasiwi, Sany; Wijaya, Putu Yudy; Putri Trarintya, Mirah Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Better teacher performance helps provide a better education for students. Teachers must be good at educating their students optimally. This study determines how performance can be improved through servant leadership, work discipline and organizational culture. The researcher chose SMPN 4 Tegallalang Gianyar as the research location. There were 40 teachers, all of whom were selected for the sample. The data analysis technique used by researchers is multiple linear regression analysis. From the results of the analysis it was concluded that servant leadership, work discipline and organizational culture can improve teacher performance positively and significantly. Based on the proposals submitted, improving teacher performance will continue to be carried out through improving personnel management, work discipline and organizational culture. Keywords: Performance; Servant Leadership; Work Discipline; Organizational culture